On the spread of the Russian sturgeon Acipenser gueldenstaedtii (Acipenseriformes: Acipenseridae) in the Neotropics: A marine path to invade freshwater drainages in South America?. (22nd October 2018) - Chuctaya, Junior; Ferrer, Juliano; Ferrari, Augusto; Vianna, Rogério T.; Malabarba, Luiz R.
Summary: Acipenser gueldenstaedtii is a species of sturgeon described from Caspian Sea and Black Sea and their tributaries, occurring in the Eastern Atlantic, Europe and Middle East. This and other two sturgeon species have been accidentally introduced in the Rio Negro, Uruguay, a tributary of the Rio de La Plata. Recently, it has been demonstrated the presence and establishment of A. gueldenstaedtii widespread in the Rio Paraná basin, the largest tributary of the Rio de La Plata, corresponding to the second largest river drainage in the Neotropics. We herein register the presence of the species in the next northern freshwater drainage in South America, representing the first record for Brazil. We further discuss the possibility of dispersal through marine environments to other freshwater drainages in South America through the analysis of its documented occurrence and marine ecoregions in southwestern Atlantic.